Formulation and Characterization of Hydroquinone Nanostructured Lipid Carriers by Homogenization Emulsification Method. (1st June 2017) - Wu, Pey-Shiuan; Lin, Chih-Hung; Kuo, Yi-Ching; Lin, Chih-Chien
Abstract : Nanostructured lipid carrier (NLC) was prepared by homogenization emulsification method and improved with modified surfactants. The properties of nanoparticles were investigated using the NLC system for hydroquinone (HQ) as a model drug and by increasing the light stability of hydroquinone. The optimized condition of NLC in stirring was 1200 rpm, the homogenized speed was 8000 rpm, solid oil to liquid oil ratio was 3 : 7, and lecithin to surfactant ratio was 3 : 1. The particle size was 393.30 ± 28.23  nm and the encapsulation efficiency was 22.13 ± 2.66 %. The zeta-potential of HQ-NLC was better than −30 mV. In the thermogravimetric analysis (TGA) studies, adding of PLANTACARE 2000 UP for HQ-NLC has better heat resisting property than the HQ-NLC only. The addition of PLANTACARE 2000 UP to NLC shows better permeability (125.10%) than that of Blank. In the stability studies, the HQ-NLC after UVA/UVB irradiation has better inhibition rate (34.25%) than that of the Blank. In the present study, NLC system has successfully improved the light stability and the skin permeability of active compound. Therefore, the NLC might be a potential delivery vehicle for transdermal products in the future.